2016
DOI: 10.1016/j.ygeno.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific transcription factor binding in liver and cervix cells unveils many likely drivers of GWAS signals

Abstract: Genome-wide association studies (GWAS) point to regions with associated genetic variants but rarely to a specific gene and therefore detailed knowledge regarding the genes contributing to complex traits and diseases remains elusive. The functional role of GWAS-SNPs is also affected by linkage disequilibrium with many variants on the same haplotype and sometimes in the same regulatory element almost equally likely to mediate the effect. Using ChIP-seq data on many transcription factors, we pinpointed genetic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Since the ENCODE Project was initiated with the aim to find all functional elements in the genome, it has accumulated numerous data on chromatin and transcribed genes obtained from various cell lines and tissues, and based on these, candidate regulatory SNPs may be found. In particular, available ChIP-seq data on allele-specific binding of different transcription factors (TFs) could be considered as a clear sign that the SNPs with regulatory potential are located within the genome regions occupied by these factors [ 15 17 ]. ChIP-seq data on allele-specific binding of active chromatin marks can also provide important insights towards the localization of regulatory variants particularly in combination with allele-specific expression profiles from RNA-seq [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ENCODE Project was initiated with the aim to find all functional elements in the genome, it has accumulated numerous data on chromatin and transcribed genes obtained from various cell lines and tissues, and based on these, candidate regulatory SNPs may be found. In particular, available ChIP-seq data on allele-specific binding of different transcription factors (TFs) could be considered as a clear sign that the SNPs with regulatory potential are located within the genome regions occupied by these factors [ 15 17 ]. ChIP-seq data on allele-specific binding of active chromatin marks can also provide important insights towards the localization of regulatory variants particularly in combination with allele-specific expression profiles from RNA-seq [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study of allele-specific events of any kind seems very valuable for identifying the functional regulatory consequences of non-coding SNPs. Notably; these allow analyzing the functionality of a significant amount of SNPs utilizing a relatively small amount of experimental datasets [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gene that is responsible for a trait may be located relatively far from the GWAS associated SNPs, as the causal SNPs may modulate TF binding and TFs can act distally to regulate gene transcription. In these cases, preferential binding of a TF to one allele causes differential regulation of gene expression to confer the phenotype [ 37 ]. Several studies have provided evidence of causal relationships for gene expression mediating the association between GWAS SNPs and traits [ 16 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its wide usage, its genomic sequence and structural features have never been characterized in a comprehensive manner beyond its karyotype (Simon et al 1982;Chen et al 1993) and SNVs identified from ChIP-Seq data and 10x coverage WGS that do not take aneuploidy or CN into consideration (Huang and Ovcharenko 2015;Cavalli et al 2016). …”
Section: Discussionmentioning
confidence: 99%